The History of Torture or Inhuman and Degrading Treatment Seen from the Perspective of Human Rights The Case of Timor-Leste - Santos, Hercus Pereira Dos (Ipso Jure, 2025)
Human rights are inalienable and inherent to every individual from birth, encompassing fundamental guarantees such as the right to life, equality, security, health, image, and physical integrity. These rights exist to ensure that every human being can live with dignity, and therefore must be respected, protected, and upheld by the state. However, history shows that although human rights are theoretically innate, they have often been violated by those in power, particularly authoritarian regimes, and only gained recognition after prolonged struggles by communities against oppression. The state seeks stability and order, yet this objective can sometimes lead rulers to justify the violation of human rights. For this reason, mechanisms and advocates for human rights emerged to ensure that state power remains controlled and limited. Human rights must be integrated into constitutional and legal frameworks so that their protection becomes a national obligation. The experience of Timor-Leste under Portuguese colonization and Indonesian occupation highlights the critical importance of safeguarding human dignity and preventing the repetition of past violations. Torture and degrading treatment fundamentally contradict human rights because they harm life and dignity. In the contemporary world, human rights should not remain merely theoretical discussions but must be embedded in national laws to protect all citizens, particularly during times of conflict when violations are most likely to occur.